Arteriosclerosis in buffalo hooves—an age related change or a pathology of lameness? - Randhawa, Swaran S; Dua, K; Banga, H S; Singh, S S; Malhotra, P (The Indian Journal of Animal Sciences, 2012)
Histopathological studies of the hoof horn tissue from the solar surface were undertaken in mature buffaloes of third or more lactation after taking biopsy. Biopsy samples were taken either of the left or right hind lateral digit due to bilateral symmetry of lesions in hind lateral claws. Five of the animals were having sole hemorrhages with 1 buffalo having overgrown hoof while the other one was having under run sole in addition to sole hemorrhages in the hind lateral digits. Other 5 animals were having perfectly normal hoofs with no lesions in their hind lateral claws and were kept as healthy control. There was mild to marked proliferation of tunica media of arterioles (arteriosclerosis) in the corium resulting in partial to complete occlusion of the lumen of blood vessel in animals having sole hemorrhages. Similar alterations were also observed in the animals having healthy hooves with no lesion. Besides that, mild focal lympho- mononuclear cell infiltration was also seen in the periarteriolar area along with perivascular edema and fibroplasia in both groups. In buffaloes with overgrown hoofs, the only additional change was the presence of occasional keratin bodies in stratum spinosum layer of the hoof epidermis. It may be inferred that there was no significant histopathological differences between healthy hooves and hooves having sole hemorrhages except degenerative changes in the stratum corneum and keratin bodies in stratum spinosum layer of the epidermis in the hooves with sole lesions. Arteriosclerosis, which was considered as a typical feature in the pathogenesis of sole lesions of lameness in cattle might be an age related change not putatively a pathology of lameness in buffaloes. Moreover this is the first histopathological study on lameness in buffaloes.